Prioritas Fakir Miskin dalam Pembagian Zakat - Abbas, Afifi Fauzi (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2020)
Zakat is an amaliyah Ijmaiyah worship (worship related to economics, finance and society) and is one of the pillars of Islam which has a very vital status and function in Islamic law. Because the Koran emphasizes the obligation of zakat along with the obligation to pray. Zakat is actually: giving out part of one's assets at the command of Allah, as obligatory sadaqah for those who have been determined according to the conditions determined by the Shari'ah. Zakat is collected from people who can afford it, and given to people who are entitled to receive it. So the place to draw zakat is from rich people who have a nishab.